Estudo dos fatores relacionados à pontuação na Escala de Depressão Pós-Parto de Edimburgo - Flavia Casasanta Marini (2004)
The postpartum period is marked by biological, psychological and social changes, and is considered a time of vulnerability for the occurrence of emotional disorders in women. Depression is widely studied and affects many women during this period, affecting both the mother and the babys health. The Edinburgh Postnatal Depression Scale (EPDS) is currently the most used scale worldwide for the study of postpartum depression (PPD), it has been developed as a tool to aid in the screening of mothers who are more likely to develop the aforementioned postpartum disorder. This work was carried out to obtain information on the risk factors that may be related to increased EPDS scores during the early postpartum period and verify the EPDS scores in mothers attended at the maternity in a public hospital in Belo Horizonte- MG/Brazil. In a cross-sectional study, 110 women were submitted to an interview that evaluate socioeconomic, demographic, obstetric and psychological variables and answered the EPDS during the early postpartum period. Cut-off point 12 for EPDS depression was used. Chi-Square test was used to identify potential predictors associated with high scores on EPDS. EPDS scores of 12 were found in 28 women (25.5%). None of these women were being treated for postpartum depression. Positive predictors (p-value 0.05) for an EPDS score of 12 were: unemployment during pregnancy, presence of both emotional and physical PMS, premature birth, previous history of psychiatric disorder, poor marital relationship, less support from their partners during pregnancy, sadness, insecurity or irritability during pregnancy. These results show that the prevalence of EPDS scores of 12 was high, indicating the need for greater attention of health professionals in relation to mental health of parturients. Although a direct etiological role for postpartum depression is not certain, knowledge of risk factors may allow strategies for the prevention of affective morbidity in postnatal women.